Evaluasi Program Pembelajaran PJOK Yang Berorientasi Hots Di Sekolah Kecamatan Lubuk Pakam Tahun Ajaran 2022-2023 - Syahbandi, Fahmi; Irfan, Muhammad; Siregar, Samsuddin; Sinulingga, Albadi; Simatupang, Nurhayati (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research evaluates the HOTS-oriented PJOK learning program in Lubuk Pakam sub-district schools. This research is a mixed methods research, namely a research step combining two forms of research approaches: qualitative and quantitative. This research includes observations, questionnaires, interviews, and documentation regarding school data collection methods. The research found that the context indicators for school principals, teachers, and deputy principals were outstanding. In contrast, the input indicators in this research were in the very good category for principals, teachers, and deputy principals. This process indicator is in the "good" category because all teachers must follow HOTS-based learning, and school principals must fully support this learning. Product indicators are included in the "Good" category. However, because students' high-level thinking abilities have not been improved through HOTS, and HOTS is considered less than fluent, especially in subjects such as physical education, the principal's product indicators contain several problems. Keywords: Evaluation, HOTS, Physical Education.